Origin and beyond: Trade facilitation disaster or trade facilitation opportunity? - Brian Rankin Staples; Jeremy Harris (Asian Development Bank Institute (ADBI), 2009)
This paper explores several mechanisms by which the barriers imposed by rules of origin may be reduced through effective trade facilitation efforts. Also discussed are the functional similarities of a variety of other requirements on international trade with rules of origin, including environmental, security, and consumer safety certifications. We argue that all of these requirements rely fundamentally on the management of information regarding materials and suppliers used in the production of internationally traded goods.
Keywords: F02; F15; F23; F53; 330